DOI: 10.11606/d.10.2010.tde-21092010-160553
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da contagem de células somáticas do leite como indicador da ocorrência de mastite em vacas Gir

Abstract: MALEK DOS REIS, C. B. Avaliação da contagem de células somáticas do leite como indicador da ocorrência de mastite em vacas Gir.[Evaluation of milk somatic cell count as an indicator of mastitis occurence in Gyr cows]. 2010.122 f. Dissertação (Mestrado em Ciências)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(56 reference statements)
0
1
0
1
Order By: Relevance
“…The dairy systems with low lactose content had higher SCCs due to changes in lactose concentration as a result of the lactose being transferred from the milk to the blood. Reis (2010) observed that, in the samples with high SCCs, milk lactose content decreased due to the damage caused in the glandular epithelium. Tissue injury caused by mastitis reduces the capacity for lactose synthesis by the glandular epithelium, which, due to the central role of lactose as an osmotic regulator of milk volume of milk, affects the amount of milk produced (Harmon, 1994).…”
Section: Resultsmentioning
confidence: 95%
“…The dairy systems with low lactose content had higher SCCs due to changes in lactose concentration as a result of the lactose being transferred from the milk to the blood. Reis (2010) observed that, in the samples with high SCCs, milk lactose content decreased due to the damage caused in the glandular epithelium. Tissue injury caused by mastitis reduces the capacity for lactose synthesis by the glandular epithelium, which, due to the central role of lactose as an osmotic regulator of milk volume of milk, affects the amount of milk produced (Harmon, 1994).…”
Section: Resultsmentioning
confidence: 95%
“…Ao todo, são mais de 250 tipos de DTA relatadas; destas, a maioria se dá por infecções causadas por bactérias e suas toxinas, além de por vírus e parasitas. Já outras doenças podem ser causadas por toxinas naturais, como, por exemplo, das presentes em cogumelos venenosos, algas e peixes; ou por aquelas provenientes de produtos químicos prejudiciais ao homem, os quais contaminaram o alimento, como chumbo e agrotóxicos (REIS, 2010).…”
Section: Introductionunclassified